MANAGEMENTUL RELAŢIILOR DE COMUNICARE ÎNTR-O CLASĂ DE ELEVI - USM ADMIN (Moldova State University, 2008)
The management of communication relationships deals with design, planning, government, organization, coordina- tion, and control of interactions and communication between the actors involved in the pedagogical relationship within school context. This segment of teacher's activity represents a distinctive aspect of the usual school management and implies a number of capacities and skills observed in the inter-personal relationships established between the members of the group. There has always been managerial practice in the communication field, but the systematic and distinct preoccupation has only recently started.